USING CASE TECHNOLOGY IN THE FORMATION OF COMPUTER KNOWLEDGE IN STUDENTS - A. N. Butayev (Modern American Journals, 2026)
This article examines the pedagogical aspects of developing students’ informational knowledge and skills through the use of case-based technology. The study substantiates the importance of information competencies in the context of modern education and reveals the didactic potential of case technology. During the research, the impact of case-based instructional activities on students’ abilities to search for, analyze, and practically apply information was investigated. The findings demonstrate that case technology is an effective pedagogical tool for enhancing students’ informational knowledge and skills and provide practical recommendations for educational practice.
Keywords: Informational knowledge, informational skills, case technology, information and communication technologies, educational process, pedagogical technologies.